The Importance of Protesters’ Morals: Moral Obligation as a Key Variable to Understand Collective Action - Sabucedo, José-Manuel; Dono, Marcos; Alzate, Mónica; Seoane, Gloria (Frontiers in Psychology, 2018)
Collective action and protest have become a normalised political behaviour that in many cases defines the political agenda. The reasons why people take to the streets constitutes a central subject within the study of Social Psychology. In the literature, three precedents of protest that have been established as central to the study of this phenomenon are: injustice, efficacy and identity. But political action is also deeply related to moral values. This explains why in recent years some moral constructs have also been pointed out as predictors of collective action. Moral variables have been introduced into the literature with little consideration to how they relate to each other. Thus, work in this direction is needed. The general aim of this research is to differentiate moral obligation from moral norms and moral conviction, as well as to compare their ability to predict collective action. In order to do so, the research objectives are: a) conceptualise and operationalise moral obligation (Study 1, N= 171); b) test its predictive power for intention to participate in protests (Study 2, N= 622); and c) test moral obligation in a real context (Study 3, N= 407). Results are encouraging, showing not only that moral obligation is different to moral conviction and moral norm, but also that it is a more effective predictor working both for intention and real participation. This work therefore presents moral obligation as a key precedent of protest participation, prompting its future use as a variable that can enhance existing predictive models of collective action. Results regarding other variables are also discussed.